Additional left atrial posterior wall ablation using pulsed field ablation as a safe and feasible treatment option for persistent atrial fibrillation patients. (19th May 2022) - Lisica, L; Sikiric, I; Katic, J; Komic, L; Breskovic, T; Jurisic, Z; Anic, A
Abstract: Funding Acknowledgements: Type of funding sources: Public hospital(s). Main funding source(s): University Hospital Center Split Background: Catheter ablation in persistent (PeAF), and especially long-standing persistent AF (ls-PeAF) patients often requires ablation beyond pulmonary vein isolation (PVI) (1). Adjunctive ablation of the left atrial posterior wall (LAPW) may improve outcomes of PeAF patients but has been limited by the difficulty of achieving lesion durability and concerns of thermal damage of nearby structures. Pulsed field ablation (PFA) is a new, nonthermal ablative modality, with proven myocardial ablative efficacy, quick energy delivery, and a favorable safety profile, which makes PFA suitable for the LAPW ablation (2). Purpose: We aimed to report the safety profile, intraprocedural parameters, and acute success rate of LAPW ablation in a regular clinical setting with the CE-marked PFA platform. Methods: This was a prospective observational study on the safety and feasibility aspects of LAPW ablation with the PFA in PeAF and ls-PeAF patients. The safety endpoints included the percentage of clinically relevant complications, including stroke/TIA, atrioesophageal fistula, cardiac tamponade, myocardial infarction, diaphragmatic paralysis, and death in the first 30-days post-procedure. Acute ablation success was confirmed with electroanatomical mapping (EAM). Ablation was performed using 2.0 kV biphasic waveforms, 2 deliveries for each application site. The lesion set depended on the patient's AF ablation history, LA size, and anatomy. After LA mapping and PVI or PVI touch-up (index or re-do procedure), 2 anchor lesions per vein extending to the LAPW were deployed. A lesion set was then performed between the anchor lesions on the LAPW (upper and lower row) with the catheter in a flower configuration and the intention of 75% overlap for the neighbouring application sites at 3D EAM. Results: Twenty-three patients (87% men) received PFA LAPW ablation. The age median was 64 (Q1-Q3: 56.5-71) years. 52% had ls-PeAF and 65% had previous ablation. The median LA diameter was 47 mm (Q1-Q3: 46-52 mm). The safety endpoints did not occur in any of the patients. The LA ablation catheter dwell time median for the index and re-do procedure was 39.5 (Q1-Q3: 31-42.25) and 18 (Q1-Q3: 16-21) minutes. The median time for LAPW ablation was 10 (Q1-Q3: 8-12) minutes. The median number of application sites on the upper and lower posterior wall was 6 (Q1-Q3: 5-7) and 6 (Q1-Q3: 5-7), respectively. Acute ablation success was 100% in terms of completed box lesion, and LAPW electrical activity loss. In a single case, first-pass ablation was not achieved, but additional delivery under intracardiac echocardiography guidance resulted in the electrical silence of the targeted segment. Conclusion: LAPW ablation with PFA is safe, quick and results in excellent acute isolation rates in PeAF patients. Posterior wall ablation with PFA is not a time-consuming procedure which is an important aspect for real-world PeAF and ls-PeAF patients who are often fragile.